Effect of Various Levels of NPK Fertilizer on the Yield Attributes of Soybean (Glycine max L.) Varieties - Perkasa, Achmad Yozar; Utomo, Utomo; Widiatmoko, Teguh (Journal of Tropical Crop Science, 2016)
Indonesian soybean production can only meet about 30% of national demand. Efforts to increase soybean production include the use of improved seed quality and fertilizer application. The aims of this research were to 1) examine the responses of six genotype soybeans to the application of different doses of NPK fertilizer; 2) determine the seed protein content of the six soybean genotypes following NPK application; 3) determine the interaction between soybean genotypes with NPK doses in affecting growth and yield. This research was conducted under a plastic house at the Faculty of Agriculture, University of Jenderal Soedirman, Central Java, Indonesia. The experiment was arranged in a randomized block design with three replications using six soybean varieties and four levels NPK fertilizer. Soybean varieties tested were “L/S: B6-G1” (V1), “L/S:B6-G3” (V2), “L/S:B6-G4” (V3), “Grobogan” (V4), “Burangrang” (V5), and “Argomulyo” (V6). Four levels NPK fertilizer tested were: without fertilizer (N0), 0.6 g per plant (N1) 1.2 g per plant (N2), and 18.g per plant (N3), or 0, 100, 200 and 300 kg.ha-1. “L/S: B6-G1” had the greatest number of seeds per plant (184) following treatment with 300 kg.ha-1 of NPK. The seed protein content increased with the increase doses of NPK. “Argomulyo” treated with NPK at 300 kg.ha-1 had the highest seed protein content (34.5%). Soybean responses to NPK treatment differed with varieties, particularly in the number of fl owers per plant, number of seeds per plant, grain weight per plant and seed protein levels.